2004
DOI: 10.1055/s-2004-835838
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of 3-O-Methylquercetin on Ovalbumin-Induced Airway Hyperresponsiveness

Abstract: Rhamnus nakaharai Hayata (Rhamnaceae) has been used as a folk medicine in Taiwan for treating constipation, inflammation, tumors, and asthma. 3-O-Methylquercetin (3-MQ), a main constituent of the plant, has been reported to inhibit total cAMP- and cGMP-phosphodiesterase (PDE) of guinea pig trachealis at low concentrations. 3-MQ has been also reported to more selectively inhibit PDE3 than PDE4 with a low K(m) value. Therefore we were interested in investigating its suppressive effects on ovalbumin (OVA)-induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The contractions of the spontaneously beating right atria were measured according to the method described by Ko et al (10), which was slightly modified. Subsequent to the baseline contraction of the spontaneously beating right atria becoming stable, the contractile tension was assessed in response to the cumulative addition of (-)SPFF, (±)SPFF and (+)SPFF in final concentrations ranging from 10…”
Section: Determination Of Cyclic Adenosine Monophosphate (Camp) Levelmentioning
confidence: 99%
“…The contractions of the spontaneously beating right atria were measured according to the method described by Ko et al (10), which was slightly modified. Subsequent to the baseline contraction of the spontaneously beating right atria becoming stable, the contractile tension was assessed in response to the cumulative addition of (-)SPFF, (±)SPFF and (+)SPFF in final concentrations ranging from 10…”
Section: Determination Of Cyclic Adenosine Monophosphate (Camp) Levelmentioning
confidence: 99%
“…Previous reports have described several fl avonoids that have potent anti-allergic effects in murine models of asthma [12][13][14]. Quercetin, a fl avonoid found in Abstract.…”
mentioning
confidence: 99%
“…Furthermore, an epidemiologic study found that a higher intake of flavonoids was associated with a lower incidence of asthma [44]. In experimental models, oral administration of flavonoids has been demonstrated to prevent allergic diseases including asthma, anaphylaxis, food allergies and atopic dermatitis [16, 17,32,33,34,35,36,37]. This study showed that the ocular symptoms were reduced in the EMIQ group.…”
Section: Discussionmentioning
confidence: 71%
“…We and others have shown that some kinds of flavonoids including apigenin, fisetin, luteolin and quercetin suppress the expression of Th2-type (IL-4, IL-5 and IL-13) [13, 14], proinflammatory cytokines [31] and CD40 ligand [15] in basophils or in mast cells. In addition to these in vitro antiallergic activities, studies with allergic animal models have demonstrated that flavonoids exert preventative and therapeutic effects by modifying Th2-type cytokine expression and suppressing IgE elevation [16, 17,32,33,34,35,36,37]. In our study we measured the serum levels of cytokines and chemokines before and after the study but found no significant reduction in Th2 cytokines (IL-4, IL-5 and IL-13), chemokines (eotaxin) or IgE concentration as a result of EMIQ intake except for TARC (fig.…”
Section: Discussionmentioning
confidence: 99%